Al-Ḥabīb Sālim Ibn Jindān wa Ḥujjatuhu fī Istiḥbāb al-Qunūt: Dirāsah wa Taḥqīq li Makhṭūṭ Iʿlām al-Nashr fī Bayān Aḥkām Qunūt al-Fajr - Anam, Khaerul; Al Munawar, Said Agil Husin (Al-Zahra : Journal for Islamic and Arabic Studies, 2024)
This research aims to study and critically edit the manuscript I‘lam al-Nashr fī Bayān Aḥkām Qunūt al-Fajr by Al-Ḥabīb Sālim bin Jindan (d. 1969 CE) and to introduce him as a prominent scholar in hadith and history from 20th-century Indonesia. The research methodology includes a comparative analysis of two manuscript copies of this book obtained from the Al-Fakhriyah Library. The study documents the differences between the two manuscripts, conducts takhrij (critical analysis) of Qur'anic verses and hadiths, and provides explanations for uncommon words and terms. Additionally, this study employs a descriptive approach by gathering relevant references from various libraries to validate the information contained in this book. The findings reveal that the critical edition of I‘lam al-Nashr fī Bayān Aḥkām Qunūt al-Fajr has been completed, establishing the authenticity of the book's title and its attribution to Al-Ḥabīb Sālim bin Jindan. This book was composed as a rebuttal to the work of Shaykh Aḥmad Ḥasan al-Hindī, who denied the Sunnah of performing Qunūt during the Fajr prayer. In his book, Al-Ḥabīb Sālim addresses these objections with strong evidence, robust arguments, and a detailed and scholarly writing style.